Complete works of Kalidasa - Kalidasa; Chaturvedi, Sudhanshu (Thrissur Geetha, 2001)
The special feature of this publication is that the author illuminating and exhauistive introduction giving an insight in to Kalidasa poetic mind and into the heart of his various characters along with a compartive study of Kalidasa's with reference to ou
Keywords: Kalidasa-Collections; Literature-Collections; Anthologies